Enhancing the Energy‐Conversion Efficiency of Solid‐State Dye‐Sensitized Solar Cells with a Charge‐Transfer Complex based on 2, 3‐Dichloro‐5, 6‐dicyano‐1, 4‐benzoquinone. Issue 4 (27th December 2017) - Wang, Weihan; Yang, Xichuan; Li, Jiajia; Wang, Haoxin; An, Jincheng; Zhang, Li; Jiang, Xiao; Yu, Ze; Sun, Licheng
Abstract: As a champion hole‐transporting material (HTM), 2, 2′7, 7′‐tetrakis‐( N, N ‐di‐ p ‐methoxyphenylamine)‐9, 9′‐spirobifluorene (Spiro‐OMeTAD) has been widely used in solid‐state dye‐sensitized solar cells (ssDSCs). Owing to the low conductivity of Spiro‐OMeTAD, a chemical doping strategy is commonly used to enhance its hole‐transporting properties. In this study, we report a strong electron acceptor, 2, 3‐dichloro‐5, 6‐dicyano‐1, 4‐benzoquinone (DDQ) as an additive for Spiro‐OMeTAD along with its application in ssDSCs. We show that the conductivity of Spiro‐OMeTAD increases from 5.31×10 −5 to 2.22×10 −4  S cm upon the addition of 0.04 % DDQ, and the power conversion efficiency (PCE) of the ssDSCs also increases. By utilizing a donor–π–acceptor sensitizer with a high coefficient and an HTM with an optimized doping ratio, we were able to achieve a high PCE of 6.37 % for the ssDSCs under 100 mW cm −2 AM1.5G simulated illumination, in comparison to the PCE of the pristine device, which was only 3.50 %. An increase in the application of benzoquinone‐based materials for organic electronics is expected, especially for solar‐cell applications. Abstract : Power play : To enhance the conductivity of the hole‐transporting material (HTM) in solid‐state dye‐sensitized solar cells (ssDSCs), a strong electron–acceptor termed DDQ is used. By utilizing a donor–π–acceptor sensitizer with a high coefficient and an HTM with an optimized doping ratio, an excellent power conversion efficiency (PCE) of 6.37 % for the ssDSCs under standard simulated illumination is achieved, whereas the PCE of the pristine device is 3.50 %.